THU0227 Adolescent and Young Adult Care in Adult Rheumatology Clinics. (15th July 2016) - Bruce, E.; Fox, J.; Watson, P.; McDonagh, J.
Abstract : Background: The importance of transitional care for young people from paediatric to adult rheumatology is well established. However, in most rheumatology departments there will be a significantly larger cohort of older adolescents and young adults (AYAs) that enter adult services de-novo than will have transitioned from paediatric services. Objectives: Our aim was to evaluate AYA care within adult Rheumatology clinics, in particular focusing on use of the HEEADDSS psychosocial interview. Methods: A review of clinical correspondence for patients aged 16–25yrs attending adult rheumatology clinics at University Hospital of South Manchester, between February 2015 and May 2015 was undertaken. Data collected included demographics, diagnosis and evaluation of documentation of the components of the HEEADDSS screen. Results: 193 appointments were issued for 16–25yr olds, representing 5% of the total number of appointments. 103 were new referrals, with a majority from general practice. Age distribution was even, over two thirds were female. The "did not attend" rate was 10%. 36 had a confirmed inflammatory condition, 27 were under investigation for a possible inflammatory arthritis and 47 had a non inflammatory condition. Of the HEEADDSS criteria the most often documented was education/employment at 31%, with exercise at 19%. Conclusions: The AYA group is well represented within this secondary care setting. Documentation of the HEEADDSS criteria was suboptimal. There may be wider implications of this on health outcomes. The first step towards improving care for this cohort is to establish an awareness within the adult team of the particular needs of this patient group, AYA health is not just a concern for paediatric rheumatologists. Disclosure of Interest: None declared